Baja (no alta) Ira Rasgo es una fortaleza personal en adolescentes - Alcázar-Olán, Raúl José; González-Fragoso, Claudia; Jiménez-Rodríguez, David; Rojas-Solis, José Luis (Acción Psicológica, 2018)
Low trait anger, the tendency to stay calm in order to cope with frustrating everyday situations, is associated with mental health and positive outcomes. Its counterpart is high trait anger, defined as intense and chronic irritability, which usually has detrimental effects on the individuals and their relationships. The purpose of this study was to test three hypotheses in adolescents with high (n = 94) and low trait anger (n = 140), with a mean age of 13.06 (SD = 0.77). Hypotheses 1 and 2 addressed the parents’ behavior (parenting practices), and hypothesis 3 assessed social skills, anger and aggression. In particular, compared to adolescents with high trait anger, those with low trait anger: 1) experience less imposition and psychological control (i.e., less negative parenting) from both, mother and father; 2) experience more communication, autonomy, and behavioral control (i.e., more positive parenting) from mother and father; and 3) present more social skills, reflected in lower levels of anger-out, lower aggression toward other individuals, and higher levels of anger self-control. The findings, as a result, supported the three hypotheses. Aggression and social skills did not differ according to gender. However, female participants experienced higher levels of trait anger than did male participants.